2012
DOI: 10.1016/j.jamcollsurg.2012.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Laparoscopy for Elective Colorectal Resection: A Report from the Surgical Care and Outcomes Assessment Program

Abstract: Background The purpose of this study was to evaluate the adoption of laparoscopic colon surgery and assess its impact in the community at large. Study Design The Surgical Care and Outcomes Assessment Program (SCOAP) is a quality improvement (QI) benchmarking initiative in the Northwest using medical record-based data. We evaluated the use of laparoscopy and a composite of adverse events (CAE; death or clinical reintervention) for patients undergoing elective colorectal surgery at 48 hospitals from 4th quarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 39 publications
(52 reference statements)
1
35
2
2
Order By: Relevance
“…Laparoscopic procedure has been associated to shorter hospital stay, faster canalization, reducing post-operative analgesic therapy, earlier return to normal daily activities and good integrity of abdominal wall (3,5,6). To maximize lymph nodes yields is essential to perform a surgical procedure that comprehends extended lymphadenectomy, extra-mesenteric lymph node dissection, high arterial ligation and complete mesocolic excision (9).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic procedure has been associated to shorter hospital stay, faster canalization, reducing post-operative analgesic therapy, earlier return to normal daily activities and good integrity of abdominal wall (3,5,6). To maximize lymph nodes yields is essential to perform a surgical procedure that comprehends extended lymphadenectomy, extra-mesenteric lymph node dissection, high arterial ligation and complete mesocolic excision (9).…”
Section: Discussionmentioning
confidence: 99%
“…8 Data from the Surgical Care and Outcomes Assessment Program (SCOAP) subsequently demonstrated an increase from 23.3% in 2005 to 41.6% in 2010. 9 Part of the challenge arises from the incongruity between the quality of surgery required for good oncological outcomes and the technology of available equipment. For example, the ability to achieve appropriate traction and precise dissection in the pelvis during laparoscopic total mesorectal excision (TME) has been limited by the restrictive single-jointed movements of straight-shaft laparoscopic instruments.…”
Section: Introductionmentioning
confidence: 99%
“…21,30,32,33 Laparoscopy and Single Ventricle Physiology Over the last two decades, laparoscopic surgery has grown exponentially in both the adult and pediatric populations. [34][35][36] Laparoscopic surgery exposes a patient to different physiologic effects than traditional open surgery. 37,38 In adults, studies have shown that the increased intraabdominal pressure necessary in laparoscopic surgery can have a significant impairment on cardiac septal wall motion and causes a decrease in cardiac index.…”
Section: Interstage Concernsmentioning
confidence: 99%